Cardiovascular Implications in Idiopathic and Syndromic Obesity in Childhood: An Update - Delvecchio, Maurizio; Pastore, Carmela; Valente, Federica; Giordano, Paola (Frontiers in Endocrinology, 2020)
Childhood obesity is a modern worldwide epidemic with significant burden for health. It is a chronic metabolic disorder associated with multiple cardiovascular risk factors such as dyslipidaemia, hypertension, stroke, and insulin resistance. Many obese adolescents remain obese into adulthood, with increased morbidity and mortality. As childhood obesity is a risk factor for adult obesity, the childhood obesity-related disorders account for an increased risk of cardiovascular consequences in adults, in addition to the effects already exerted by the fat mass in adulthood. A lot of papers describe the cardiovascular implications of idiopathic obesity, while there are few data about syndromic obesity, due to small sample size, not homogeneous phenotypes, and younger age at death. The aim of this mini-review is to give a comprehensive overview on cardiovascular implications of idiopathic and syndromic obesity, to allow the reader a quick comparison between them. Similitudes and differences are highlighted.